Comparing root exudate collection techniques: An improved hybrid method. (October 2021) - Williams, Alex; Langridge, Holly; Straathof, Angela L.; Fox, Graeme; Muhammadali, Howbeer; Hollywood, Katherine A.; Xu, Yun; Goodacre, Royston; de Vries, Franciska T.
Abstract: 1. Plant-microbe interactions are critical for ecosystem functioning and drive rhizosphere processes. Root exudates are an important soil carbon (C) input, as well as a mechanism for communication between plants and rhizosphere microbes, but are notoriously difficult to extract and characterise. Common methods produce either substantial noise from the soil or do not mimic natural systems. Optimising methods for root exudate collection in soil is crucial for advancing our understanding of root-microbe interactions under changing environmental conditions. 2. Hybrid root exudate collection methods, where plants are grown in soil and transferred to hydroponics for exudate collection after root washing, might offer an ecologically relevant alternative to existing approaches. However, this method causes potential root damage as well as osmosis and subsequent leaking of cell contents. Here, we assessed different 'root recovery' periods after root washing and before hybrid root exudate collection, by comparing root exudate quantity and quality with both damaged root extracts and with leachates collected from the intact root-soil system. This was done across three common grassland species representing three functional groups. 3. We found that root exudate profiles of the shortest recovery period (0 days) were similar to damaged root extracts and were very high in C. With an increasing period of root recovery, profiles were more similar to leachates collected from the intact root-soil system, and C concentrations decreased. While both hybrid and leachate collection methods separated species by their root exudate profiles, the hybrid method was less variable in terms of the amount of C measured and provided a more diverse and abundant metabolome with better identification of metabolites. 4. Our results show that a recovery period after root washing of at least 3 days is critical to prevent root damage bias in hybrid collection methods, and that our hybrid method yields exudates that discriminate between species. Our data also suggest that exudates collected with this hybrid method are ecologically valid, which is vital for gaining a mechanistic understanding of their role in ecosystem functioning. Highlights: Root-washing method is suitable for ecologically sound root exudate collection. It allows accurate measures of exudate quantity and composition. Damage affects must be accounted for and use of a recovery protocol is recommended. The method permits identification of metabolite specificity between species. Leachate complements, provides rhizosphere chemical info and species specificity. Abstract : Tweetable abstract: We introduce a root-washing method for ecologically sound root exudate collection to minimise root damage and distinguish species.